PEMILIHAN HARI BAIK PERKAWINAN MASYARAKAT AENG PANAS SEBAGAI UPAYA PENCEGAHAN PERCERAIAN PERSPEKTIF MAQASHID AL-SYARI’AH - Ahmad Hafidz, (JIL : Journal of Indonesian Law, 2024)
This article explains a Javanese tradition, namely in the form of choosing a good day for marriage that occurs in Aeng Panas Village, Pragaan, Sumenep, in this case the people of Aeng Panas Village think that for couples who are going to get married they must look for a good day, because the selection of a good day in marriage according to the calculation has a positive impact and a negative impact, Positive impacts can launch and bring happiness to the bride and groom, the negative impact can bring bad luck and bad luck. Meanwhile, in the view of the Islamic context, it is not explained that there is an unlucky day or a bad luck bearer. This study uses a qualitative research approach using ethnography, which is research that describes a culture from a group of people, the culture in question is to understand and study the life of the individual studied through maqashid al-syariah. Based on research, it was found that the people of Aeng Village are hot when they are going to carry out a wedding first, they will go to their teacher or elders in the village who understand in terms of choosing a good day for the bride and groom. The background for choosing a good day is as a medium (washilah) for the safety of one's household, as well as maintaining traditions that have been passed down from generation to generation from ancestors. From the perspective of maqashid sharia, choosing a good day as one of the marriage rites is included in the category of al-maslahat tahsiniyyat (tertiary). The tradition contains positive values, namely for the safety of his household and to avoid divorce.